Rancang Bangun Aplikasi Kasir Dan Stok Barang Di Apotek Munawwarah Farma Berbasis Website - Muhammad Iqbal; Djamaludin Djamaludin; Muhammad Khoirul Anam (JURNAL ILMIAH FAKULTAS TEKNIK, 2023)
Background: Information and communication technology enables the collection of information quickly and efficiently, enabling better data management from company locations. Additionally, this technology can help businesses in formulating the best strategies and policy owners by acting as a catalyst for accurate decision making. After talking to and observing store owners, it became clear that they faced a number of difficulties in running their businesses on a daily basis, especially when it came to tracking sales transactions and managing inventory. This analysis shows that there has never been an application for managing sales transactions and inventory. To manage transactions more quickly, the Munawwarah Farma Pharmacy store must have a computerized system that supports the sales process, so that it can help the transaction process run quickly and precisely. Method: In this research, researchers implemented the Agile Software Development method in a web-based sales and stock recording application. Purpose: This application also has a feature for managing access rights so that shop owners can regulate which pages can be accessed by employees or cashiers, so that they can maintain the security of stock data to avoid unwanted things. Research Results: Based on the design results of the implementation of the Agile Software Development method in the web-based application for sales and stock of goods at the Munawwarah Farma Pharmacy shop which has a sales transaction feature using a barcode scanner and also in this application there are details of sales and purchases which can help shop owners to can manage stock of goods easily.